2022
DOI: 10.3390/geriatrics7060130
|View full text |Cite
|
Sign up to set email alerts
|

Attitude towards Older People According to Sociodemographic and Educational Variables in Students of a Chilean University

Abstract: Current evidence suggests that attitude towards older people may be associated with sociodemographic and educational variables; hence, a positive attitude towards older people is key when training new university professionals. However, there is little evidence of this association in Chilean university students. The objective was to analyze students from a Chilean university’s attitudes towards older people, according to sociodemographic and educational variables. Analytical and cross-sectional study; 515 stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…This finding is supported by the study done in Chile, which reported that older students had a better attitude towards geriatric care. 20 Significant differences in attitude scores by age group were also observed in a Nigerian study. 19 Older students may have more experience which makes them motivated toward a caring attitude endorsed by their social environment and education.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…This finding is supported by the study done in Chile, which reported that older students had a better attitude towards geriatric care. 20 Significant differences in attitude scores by age group were also observed in a Nigerian study. 19 Older students may have more experience which makes them motivated toward a caring attitude endorsed by their social environment and education.…”
Section: Discussionmentioning
confidence: 71%
“… 6 On the contrary, the study conducted in Chile also showed that the majority (61.2%) of undergraduate students generally perceived themselves with a low-level positive attitude. 20 The difference may be due to a variation in the study setting, study population, the question used to assess attitude, and a cut-off point. The study participants in this study may not had adequate exposure to geriatric care due to the absence of a separate geriatric care center in this study setting.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for this outcome could be that generally females tend to be more sympathetic and demonstrate empathy towards the older patients as well as they might show more attention while treating their patients. 37 However, no significant difference was noted in any of the factors while comparing the gender in German 23 and Brazilian 20 versions of the scale, while in the French version 22 a statistically significant difference was noted in which male students recorded lower scores in component three regarding the education around older patient care. This study also documented that students who did not live with their family members exhibited significantly higher "ageist" scores than those who resided in their own homes with their family members for Factor 5.…”
Section: Discussionmentioning
confidence: 89%
“…This finding aligned with other validation studies performed in the USA 33 and India 25 in which female students exhibited less ageist attitudes. A possible explanation for this outcome could be that generally females tend to be more sympathetic and demonstrate empathy towards the older patients as well as they might show more attention while treating their patients 37 . However, no significant difference was noted in any of the factors while comparing the gender in German 23 and Brazilian 20 versions of the scale, while in the French version 22 a statistically significant difference was noted in which male students recorded lower scores in component three regarding the education around older patient care.…”
Section: Discussionmentioning
confidence: 99%